Moroccan Teachers’ Acceptance and Use of Microsoft Teams During COVID-19 - Saki , Ousama; DARHOUR, Hanane; Sibouih, Said; Elfiaa, Abdelwahab (International Journal of Language and Literary Studies, 2024)
This study examines Moroccan teachers’ acceptance and use of Microsoft Teams, Morocco’s official educational platform for distance education. To investigate the factors that affect teachers’ decision to accept and use this platform, the study employs an exploratory quantitative research design and adopts the Unified Theory of Acceptance and Use of Technology (UTAUT) as the conceptual framework. The overall results indicate that many participants never used Microsoft Teams, and a significant proportion expressed uncertainty about its utility. Generally, the participants had positive perceptions of this educational platform in terms of its user-friendliness, yet limited social influence and lack of facilitating conditions hampered its widespread use. The study emphasizes the significant role of the civic responsibility construct as a driving force for teachers’ motivation to use Microsoft Teams. Based on these results, the study provides some recommendations to policymakers and education stakeholders on how to boost teacher acceptance and use of Microsoft Teams.